Development of improved methods for the characterisation of organic chemicals emitted into indoor air by building and furnishing products - Brown, Veronica M. (Cranfield University, 2013)
A wide range of organic compounds are released from building and furnishing products and these have the potential to adversely affect indoor air quality. There are growing international requirements for testing and controlling these emissions for the protection of public health. The test methods require specialist analytical chemistry facilities based on thermal desorption/gas chromatography/mass spectrometry (TD/GC/MS). This project has addressed the need for better performance and greater automation of the analysis, as well as development of simpler screening tests. A variety of products were tested using screening techniques, with an emission cell method being used as a reference test. Short duration tests, using a micro-scale chamber at slightly elevated temperature, were shown to have the potential to predict emissions occurring during longer term reference tests. Multi-sorbent air sampling tubes, that have the potential to extend the volatility range of compounds determined by a single TD/GC/MS analysis, were compared with Tenax TA tubes specified by current standard methods. This showed no difference in performance for the range of compounds for which Tenax is optimal, with improved performance for a number of more volatile compounds. The determination of formaldehyde was investigated using 2-hydroxymethylpiperidine as a derivatising agent, followed by TD/GC/MS. The results showed the possibility of this method being developed as an alternative to the current standard method that involves solvent elution and liquid chromatography. The performance of a newly developed time-of-flight mass spectrometer was compared with a standard quadrupole instrument. This showed its potential, with the use of re-collection, to extend the concentration range of compounds quantified from a single air sample, of particular benefit for the determination of carcinogens. New compound identification software was applied to increase automation of analysis of the TD/GC/MS data. Good correlation with manual processing was achieved, demonstrating the possibility of routine application to material emissions testing.
Keywords: VOCs; VVOCs; SVOCs; Formaldehyde; Screening tests; Tenax; Multi-sorbent; Material emissions; Thermal desorption/gas chromatography/mass spectrometry; TD/GC/MS; Time-of-flight; TOF; MS; TargetView Software